The Bloomsbury handbook of electronic literature / edited by Joseph Tabbi. - Tabbi, Joseph, 1960- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"The digital age has had a profound impact on literary culture, with new technologies opening up opportunities for new forms of literary art from hyperfiction to multi-media poetry and narrative-driven games. Bringing together leading scholars and artists from across the world, The Bloomsbury Handbook of Electronic Literature is the first authoritative reference handbook to the field. Crossing disciplinary boundaries, this book explores the foundational theories of the field, contemporary artistic practices, debates and controversies surrounding such key concepts as canonicity, world systems, narrative and the digital humanities, and historical developments and new media contexts of contemporary electronic literature. Including guides to major publications in the field, The Bloomsbury Handbook of Electronic Literature is an essential resource for scholars of contemporary culture in the digital era."--